APEX Calculus - Hartman, Gregory; Heinold, Brian; Siemers, Troy; Chalishajar, Dimplekumar; Bowen, Jennifer; Open Textbook Library (Open Textbook Library, 2014)
This text comprises a three-text series on Calculus. The first part covers material taught in many "Calc 1" courses: limits, derivatives, and the basics of integration, found in Chapters 1 through 6.1. The second text covers material often taught in "Calc 2:" integration and its applications, along with an introduction to sequences, series and Taylor Polynomials, found in Chapters 5 through 8. The third text covers topics common in "Calc 3" or "multivariable calc:" parametric equations, polar coordinates, vector-valued functions, and functions of more than one variable, found in Chapters 9 through 14. More information, including free downloads of .pdf versions of the text, is available at www.apexcalculus.com.
Chapter 1: Limits -- Chapter 2: Derivatives -- Chapter 3: The Graphical Behavior of Functions -- Chapter 4: Applications of the Derivative -- Chapter 5: Integration -- Chapter 6: Techniques of Antidifferentiation -- Chapter 7: Applications of Integration -- Chapter 8: Sequences and Series -- Chapter 9: Curves in the Plane -- Chapter 10: Vectors -- Chapter 11: Vector Valued Functions -- Chapter 12: Functions of Several Variables -- Chapter 13: Multiple Integrations -- Chapter 14: Vector Analysis
In English.
Description based on print resource
Keywords: Mathematics -- Textbooks